Universidades Corporativas: proposição de um modelo conceitual - Macedo, Ricardo Baiocchi de (2001)
The aim of the present study is to develop a Corporate University Model, that could be adapted to great national companies, contributing pragmatically to recent developments in corporate education. For this reason, a larger understanding of the phenomenon that represents the appearance of those entities in the dynamics of the managerial education process, was sought, through the study of its main characteristics, a distinction between them, academic universities and also the traditional process of corporate education, targeting a set of specific requirements for successful implementation. The study was developed with a qualitative focus, aiming to analyze the theories and models now existent, signaling to educational professionals and company executives important aspects in its execution. This led to an overview of the themes that generate new alternatives for those who need to make decisions related to the subject. A reading of the publishments on higher education in Brazil and the Brazilian university model, on managerial education and what could be found on corporate universities, was carried out. Soon after, researches were made in companies that had similar implemented models or those in the process of implementation, seeking to know its main differences, likenesses and peculiarities. Meticulous study and the attentive analysis of the whole research material collected led to the proposition of the model, which was implanted in January of 2001, in Caixa Econômica Federal.